Zagadnienie czynu ciągłego a nieumyślność - Kanty, Tomasz (PRAWO i WIĘŹ, 2024)
The paper deals with the question of unintentionality in the context of a continuous act. The results of the doctrine so far indicate the impossibility of committing a continuous act unintentionally. However, an analysis of the current jurisprudence encourages the consideration of a different concept, in which the intention referred to in the provision of Article 12 does not refer to the act as such, but to the “continuity” of the act itself. This is shown by an analysis of the individual provisions of the Criminal Code that use the concept of intent.